2022
DOI: 10.1021/acsami.2c04752
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Polythiophene-Conjugated Polyelectrolyte-Based Memristors for Transient Electronics

Abstract: The key to protect sensitive information stored in electronic memory devices from disclosure is to develop transient electronic devices that are capable of being destroyed quickly in an emergency. By using a highly water-soluble polythiophene-conjugated polyelectrolyte PTT–NMI+Br– as an active material, which was synthesized by the reaction of poly­[thiophene-alt-4,4-bis­(6-bromohexyl)-4H-cyclopenta­(1,2-b:5,4-b′)­dithiophene] with N-methylimidazole, a flexible electronic device, Al/PTT–NMI+Br–/ITO-coated PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Polymer memory devices/memristors have attracted considerable attention in recent years. A flexible and water-soluble transient electronic device that exhibits both nonvolatile rewritable resistive random-access memory (RRAM) performance and memristive properties was fabricated by Wang et al The device had the structure of Al/PTT-NMI + Br – /ITO-coated PET, where PTT-NMI + Br – is a conjugated water-soluble polyelectrolyte (Figure f). The memory and electrical switching performance of the device was evaluated in ambient conditions with the device showing a rewritable RRAM performance (with the voltage varied from 0 to ±3 V).…”
Section: Conjugated Polymer-based Transient Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer memory devices/memristors have attracted considerable attention in recent years. A flexible and water-soluble transient electronic device that exhibits both nonvolatile rewritable resistive random-access memory (RRAM) performance and memristive properties was fabricated by Wang et al The device had the structure of Al/PTT-NMI + Br – /ITO-coated PET, where PTT-NMI + Br – is a conjugated water-soluble polyelectrolyte (Figure f). The memory and electrical switching performance of the device was evaluated in ambient conditions with the device showing a rewritable RRAM performance (with the voltage varied from 0 to ±3 V).…”
Section: Conjugated Polymer-based Transient Electronicsmentioning
confidence: 99%
“…Wang et al reported the use of a water-soluble polythiophenebased conjugated polyelectrolyte in memristor devices. 111 They synthesized a highly water-soluble (up to 5.5 mg/mL) conjugated polyelectrolyte, named PTT-NMI + B − , by the reaction of poly[thiophene-alt-4,4-bis(6-bromohexyl)-4Hcyclopenta(1,2-b:5,4-b′)dithiophene] (PTT-Br) with N-methylimidazole (Figure 7f,g). PTT-NMI + B − was used to fabricate a flexible, transient information storage device consisting of Al/ PTT-NMI + Br − /ITO-coated poly(ethylene terephthalate) (PET) (Figure 7h) (also see Section 2.5).…”
Section: Dissolvable Conjugatedmentioning
confidence: 99%
“…Polyelectrolytes, have used been as water-tolerant materials in many applications, such as diodes, transistors, photovoltaic devices and memristors, where the current is carried by ions. [15][16][17][18][19][20][21] It is not only a natural insulation material, but also an ionic conducting material which is superior for use as an ionic pathway for a dielectric layer. 22,23 Xu and Wang reported water-soluble conjugated polyelectrolyte-based memristors and synapses.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Xu and Wang reported water-soluble conjugated polyelectrolyte-based memristors and synapses. 20,21 However, there is scope to improve the performance of memristors and synapses, and for a greater understanding of the working principle. In this research, we evaluated the use of positive (poly(ethyleneimine), PEI) and negative (poly(acrylic acid), PAA) polyelectrolytes as the ionic pathway layer in a memristor device with Ca 2+ doping (ITO/PEI-Ca 2+ /ITO and ITO/PAA-Ca 2+ /ITO), which was simple to prepare by spin-coating the PEI or PAA solution with Ca 2+ on to the ITO substrate followed by magnetron sputtering of the ITO as the top electrode (TE).…”
Section: Introductionmentioning
confidence: 99%
“…Some transient memory devices, in which some metals, metal oxides, perovskites, natural products, and soluble polymer matrixes were used as the device electrodes or active layer materials, have been developed for addressing these problems in the recent several years. [15][16][17][18][19][20][21][22][23][24][25][26][27] These materials either react chemically with water or dissolve in water, and consequently the corresponding devices can be destroyed rapidly.…”
Section: Introductionmentioning
confidence: 99%